How Does the Relevance of Firm-Generated Content to Products Affect Consumer Brand Attitudes? - Yao Li; Ying Yin; Zhiqiang Wang (Journal of Theoretical and Applied Electronic Commerce Research)
Despite the growing importance of firm-generated content (FGC) on social platforms, the effect of its relevance to products on consumer brand attitudes remains underexplored. As digital platforms increasingly influence consumer decision-making, this study investigates how the relevance of FGC to products affects consumer brand attitudes. Through four experimental studies, we examine the mediating role of brand authenticity and the moderating effects of brand type (time-honored vs. new) and consumer thinking style (analytic vs. holistic). The results indicate that the relevance of FGC to products positively affects consumer brand attitudes, with brand authenticity acting as a mediating factor. Furthermore, this effect is stronger for time-honored brands and analytic-thinking consumers. These findings contribute to digital marketing literature by introducing a novel perspective on FGC and product relevance, an aspect largely overlooked in previous research. Our study also provides valuable insights for brand managers on how to leverage FGC to enhance consumer–brand interactions, particularly by aligning FGC with both brand type and consumer thinking style.